Mechanism of the Gut Microbiota Colonization Resistance and Enteric Pathogen Infection - Khan, Israr; Bai, Yanrui; Zha, Lajia; Ullah, Naeem; Ullah, Habib; Shah, Syed Rafiq Hussain; Sun, Hui; Zhang, Chunjiang (Frontiers in Cellular and Infection Microbiology, 2021)
The mammalian gut microbial community, known as the gut microbiota, comprises trillions of bacteria, which co-evolved with the host and has an important role in a variety of host functions that include nutrient acquisition, metabolism, and immunity development, and more importantly, it plays a critical role in the protection of the host from enteric infections associated with exogenous pathogens or indigenous pathobiont outgrowth that may result from healthy gut microbial community disruption. Microbiota evolves complex mechanisms to restrain pathogen growth, which included nutrient competition, competitive metabolic interactions, niche exclusion, and induction of host immune response, which are collectively termed colonization resistance. On the other hand, pathogens have also developed counterstrategies to expand their population and enhance their virulence to cope with the gut microbiota colonization resistance and cause infection. This review summarizes the available literature on the complex relationship occurring between the intestinal microbiota and enteric pathogens, describing how the gut microbiota can mediate colonization resistance against bacterial enteric infections and how bacterial enteropathogens can overcome this resistance as well as how the understanding of this complex interaction can inform future therapies against infectious diseases.